2018
DOI: 10.4172/neuropsychiatry.1000342
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive Therapy Modulates the Structural and Functional Architecture of Frontal Pole in Major Depressive Disorder

Abstract: Background:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…(Bludau et al, 2014;Gilbert et al, 2006). Previous studies have reported that depression is associated to reduced medial frontal pole volume (Bludau et al, 2016), and that decreased frontal pole volume and FC following ECT was related to therapeutic efficacy (Xu et al, 2018). The medial temporal lobes have been consistently implicated in ECT neuroimaging research and include the hippocampus and amygdala, which have shown to undergo structural changes in volume, functional connectivity, and perfusion following ECT (Leaver et al, 2016;Mulders et al, 2020;Ousdal et al, 2020;Redlich et al, 2016;Takamiya et al, 2018;Wilkinson, Sanacora, & Bloch, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…(Bludau et al, 2014;Gilbert et al, 2006). Previous studies have reported that depression is associated to reduced medial frontal pole volume (Bludau et al, 2016), and that decreased frontal pole volume and FC following ECT was related to therapeutic efficacy (Xu et al, 2018). The medial temporal lobes have been consistently implicated in ECT neuroimaging research and include the hippocampus and amygdala, which have shown to undergo structural changes in volume, functional connectivity, and perfusion following ECT (Leaver et al, 2016;Mulders et al, 2020;Ousdal et al, 2020;Redlich et al, 2016;Takamiya et al, 2018;Wilkinson, Sanacora, & Bloch, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We propose that frontal and prefrontal circuits and especially their connectivity to depression-associated regions may affect ECT outcomes not solely dependent on electrode placement. Interestingly, structural [ 63 , 64 ] and functional [ 65 , 66 ] changes following ECT have been observed within the amygdala and within the FP [ 67 ]. On a functional level, the FP may subserve an integratory role for higher-order social, emotional, and cognitive processes [ 68 , 69 ] and contribute to the development of typical symptoms associated with depression e.g.…”
Section: Discussionmentioning
confidence: 99%
“…(29,30). Previous studies have reported that depression is associated to reduced medial frontal pole volume (31) and that decreased frontal pole volume and FC following ECT was related to therapeutic efficacy (32). The medial temporal lobes have been consistently implicated in ECT neuroimaging research and include the hippocampus and amygdala, which have shown to undergo structural changes in volume, functional connectivity and perfusion following ECT treatment (5,24,26,(33)(34)(35).…”
Section: < Insert Figure 4 > Discussionmentioning
confidence: 99%